A novel application of nano-cellulose (coconut coir fibres) for the modification of mixed matrix membrane for CO2/CH4 separation - Ajay Gawali; Sapna Gawali; Snigdha Khuntia; Surendra Sasikumar Jampa; Manish Kumar Sinha (Sustainable Chemistry for Climate Action)
The present work is, for the first time, concentrated on using agricultural cellulose material as a conceivable filler in membranes for CO2/CH4 gas separation. It was possible to fabricate a better membrane with low cost and good permeability (CO2) and selectivity (CO2/CH4). The novel DANC@PEI filler is synthesized from coconut coir fibres, its surface area is very effective for gas separation. The nano-cellulose fibres (NC) were extracted from coconut coir fibres, converted into dialdehyde nano-cellulose (DANC) and functionalized with polyethyleneimine (PEI). The synthesized nano-cellulose filler DANC@PEI (1, 3, 5 wt.%) was incorporated into PSF (Polysulfone). The mixed matrix membranes (MMMs) were characterized by FTIR, TGA, SEM and XRD. The result suggested that for pure and mixed studies, the CO2 permeability in pure gas (12.21 Barrer) and mixed gas (11.35 Barrer) was increased compared to the plain PSF membrane (7.02 Barrer). The selectivity was also significantly increased due to PEI functionalization with DANC, which provides more sites for CO2 sorption, not CH4. From the observation, DANC@PEI nano-cellulose filler is a promising candidate for CO2/CH4 separation.